2018
DOI: 10.3310/hta22040
|View full text |Cite
|
Sign up to set email alerts
|

Combining optical coherence tomography with visual field data to rapidly detect disease progression in glaucoma: a diagnostic accuracy study

Abstract: Background Progressive optic nerve damage in glaucoma results in vision loss, quantifiable with visual field (VF) testing. VF measurements are, however, highly variable, making identification of worsening vision (‘progression’) challenging. Glaucomatous optic nerve damage can also be measured with imaging techniques such as optical coherence tomography (OCT). Objective To compare statistical methods that combine VF and OCT da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 113 publications
1
23
0
Order By: Relevance
“…Second, the permutation of pointwise linear regression (PoPLR) technique was used to analyze the pointwise sensitivities and PD values of each VF series. [21][22][23] PoPLR repeatedly permutes the order of VF visits in a series to give robust estimations of the likelihood of significant VF change. In our case PoPLR was performed on PD values as an indicator of worsening VF to mitigate global changes that may occur, for example, from developing cataract.…”
Section: Anonymized Recorded Data Between April 2000 Andmentioning
confidence: 99%
“…Second, the permutation of pointwise linear regression (PoPLR) technique was used to analyze the pointwise sensitivities and PD values of each VF series. [21][22][23] PoPLR repeatedly permutes the order of VF visits in a series to give robust estimations of the likelihood of significant VF change. In our case PoPLR was performed on PD values as an indicator of worsening VF to mitigate global changes that may occur, for example, from developing cataract.…”
Section: Anonymized Recorded Data Between April 2000 Andmentioning
confidence: 99%
“…This is the first study to our knowledge that has evaluated the value of including OCT imaging as an outcome measure in addition to conventional visual field testing. A recent report by Garway-Heath and colleagues 20 evaluated a method of using OCT imaging data to guide the analysis of visual field progression in glaucoma eyes. When compared to a standard event-based analysis of the visual field data, this method did not reduce the sample size requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the observations about the potential value of OCT imaging for glaucoma clinical trials may be explained by a few potential factors. Most importantly, the OCT imaging data was used to guide the visual field progression analysis in the recent report 20 , rather than being used independently as an outcome measure. This approach may not have fully capitalized on the information on disease progression provided by OCT imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garway-Heath and coworkers further developed ANSWERS to combine visual field and optical coherence tomography measurements to detect glaucomatous progression and found that this method outperformed the field-only approach. 65,66 At a specificity of 95%, the combined ANSWERS approach achieved a sensitivity of 70% to detect progression, while the field-only ANSWERS and PoPLR showed the similar sensitivity of 35%. Nevertheless, the present version of combined method failed to differentiate eyes on treatment from those not on treatment, which may therefore limit its use to evaluate treatment effects in clinical trials.…”
Section: Answersmentioning
confidence: 97%